PHYSICAL VS. DIGITAL SAFE HAVENS IN EMERGING ISLAMIC MARKETS: A COMPARATIVE ANALYSIS OF GOLD, COMMODITIES, AND CRYPTO ASSETS IN INDONESIA, MALAYSIA, AND TURKEY - Gandy Setiawan; Magita Sari; Achmad Helmi; Ahmad Rodoni (ITB AAS Indonesia Surakarta, 2026)
This study investigates the safe-haven properties of physical assets (Gold, Commodities) versus digital assets (Crypto, Shariah-compliant Tokens) for Islamic equity markets in Indonesia, Malaysia, and Turkey during the 2020–2025 monetary tightening era. Utilizing weekly data, the study employs Dummy Augmented Regression and Portfolio Weight Optimization to isolate asset correlations during extreme market downturns and simulate hedging effectiveness. The results reveal a